Replacement of dietary fish oil for Atlantic salmon parr ( Salmo salar L.) with a stearidonic acid containing oil has no effect on omega-3 long chain polyunsaturated fatty acid concentrations - Miller, MR; Nichols, PD; Carter, CG (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2007)
The worldwide increase in aquaculture production and the concurrent decrease of wild fish stocks has made the replacement of fish oil in aquafeeds an industry priority. Oil from a plant source Echium plantagineum L., Boraginaceae, has high levels of stearidonic acid (SDA, 18:43, 14%) a biosynthetic precursor of omega-3 long-chain (C20) polyunsaturated fatty acids (3 LC-PUFA). Atlantic salmon (Salmo salar L.) parr were fed a control fish oil diet (FO) or one of 3 experimental diets with 100% canola oil (CO) 100% SDA oil (SO), and a 1:1 mix of CO and SDA oil (MX) for 42days. There were no differences in the growth or feed efficiency between the four diets. However, there were significant differences in the fatty acid (FA) profiles of the red and white muscle tissues. Significantly higher amounts of SDA, eicosapentaenoic acid (20:53, EPA), docosahexaenoic acid (22:63, DHA) and total 3 FA occurred in both red and white muscle tissues of fish fed SO and FO compared with those fed CO. Feeding SO diet resulted in 3 LC-PUFA amounts in the white and red muscle being comparable to the FO diet. This study shows that absolute concentration (g/g) of EPA, DHA and total 3 have been maintained over 6weeks for Atlantic salmon fed 14% SDA oil. The balance between increased biosynthesis and retention of 3 LC-PUFA to maintain the concentrations observed in the SO fed fish remains to be conclusively determined, and further studies are needed to ascertain this. 2006 Elsevier Inc. All rights reserved.